Mastectomy patterns, but not rates, are changing in the treatment of early breast cancer. Experience of a single European institution on 2315 consecutive patients. (June 2018) - Fancellu, Alessandro; Sanna, Valeria; Cottu, Pietrina; Feo, Cladio F.; Scanu, Antonio M.; Farina, Giulia; Bulla, Antonio; Spanu, Angela; Paliogiannis, Panagiotis; Porcu, Alberto
Abstract: Background: Recent literature reports that rates of mastectomy are increasing in early breast cancer. However, data from European institutions are limited and revealed conflicting results. We report on 15-year trends of mastectomy, mastectomy plus immediate reconstruction and contralateral prophylactic mastectomy (CPM) at an academic institution. Methods: We identified women diagnosed with unilateral early breast cancer at stage 0-IIa, with tumour size ≤ 4 cm, between 2002 and 2016. Trends were assessed using the Cochrane–Armitage test. Multivariable logistic regression was used to identify factors associated with receipt of mastectomy plus immediate reconstruction. Results: A total of 2315 patients were identified. Of them, 65.7% underwent breast conserving surgery (BCS), while 34.3% underwent mastectomy as upfront surgery. Two point four per cent also received CPM. Immediate reconstruction was performed in 36.0% of patients receiving mastectomy. There was no change in trends of mastectomy over the 15 years studied (p = 0.69), as well as in trends of patients undergoing CPM ( p  = 0.44). In contrast, rates of immediate reconstruction rose significantly over the study period (from 12.2% in 2002 to 62.7% in 2016, p  < 0.0001). Women were more likely to receive mastectomy plus immediate reconstruction if they were aged 50 years or younger, or had tumours larger than 2 cm, or had non-invasive carcinoma. Conclusions: Our study suggests that rates of both mastectomy and CPM in early breast cancer are not increasing, while use of immediate reconstruction is on the rise. Highlights: Recent literature suggests that rates of mastectomy are on the rise in patients with early breast cancer. In our study there was no change in trends of mastectomy vs breast conservation. Rates of contralateral prophylactic mastectomy were not increased. Rates of immediate reconstruction were significantly increased. This is one of the largest single-institution European studies addressing the issue of mastectomy trends.